A methodological approach to correlate tumor heterogeneity with drug distribution profile in mass spectrometry imaging data. Issue 11 (25th November 2020) - Prasad, Mridula; Postma, Geert; Franceschi, Pietro; Morosi, Lavinia; Giordano, Silvia; Falcetta, Francesca; Giavazzi, Raffaella; Davoli, Enrico; Buydens, Lutgarde M C; Jansen, Jeroen
Abstract: Background: Drug mass spectrometry imaging (MSI) data contain knowledge about drug and several other molecular ions present in a biological sample. However, a proper approach to fully explore the potential of such type of data is still missing. Therefore, a computational pipeline that combines different spatial and non-spatial methods is proposed to link the observed drug distribution profile with tumor heterogeneity in solid tumor. Our data analysis steps include pre-processing of MSI data, cluster analysis, drug local indicators of spatial association (LISA) map, and ions selection. Results: The number of clusters identified from different tumor tissues. The spatial homogeneity of the individual cluster was measured using a modified version of our drug homogeneity method. The clustered image and drug LISA map were simultaneously analyzed to link identified clusters with observed drug distribution profile. Finally, ions selection was performed using the spatially aware method. Conclusions: In this paper, we have shown an approach to correlate the drug distribution with spatial heterogeneity in untargeted MSI data. Our approach is freely available in an R package 'CorrDrugTumorMSI'.